Differences in brain connectivity between older adults practicing Tai Chi and Water Aerobics: a case–control study - Port, Ana Paula; Paulo, Artur José Marques; de Azevedo Neto, Raymundo Machado; Lacerda, Shirley Silva; Radvany, João; Santaella, Danilo Forghieri; Kozasa, Elisa Harumi (Frontiers in Integrative Neuroscience, 2024)
Background This study aimed to investigate the neural mechanisms that differentiate mind–body practices from aerobic physical activities and elucidate their effects on cognition and healthy aging. We examined functional brain connectivity in older adults (age > 60) without pre-existing uncontrolled chronic diseases, comparing Tai Chi with Water Aerobics practitioners. Methods We conducted a cross-sectional, case–control fMRI study involving two strictly matched groups (n = 32) based on gender, age, education, and years of practice. Seed-to-voxel analysis was performed using the Salience, and Frontoparietal Networks as seed regions in Stroop Word-Color and N-Back tasks and Resting State. Results During Resting State condition and using Salience network as a seed, Tai Chi group exhibited a stronger correlation between Anterior Cingulate Cortex and Insular Cortex areas (regions related to interoceptive awareness, cognitive control and motor organization of subjective aspects of experience). In N-Back task and using Salience network as seed, Tai Chi group showed increased correlation between Left Supramarginal Gyrus and various cerebellar regions (related to memory, attention, cognitive processing, sensorimotor control and cognitive flexibility). In Stroop task, using Salience network as seed, Tai Chi group showed enhanced correlation between Left Rostral Prefrontal Cortex and Right Occipital Pole, and Right Lateral Occipital Cortex (areas associated with sustained attention, prospective memory, mediate attention between external stimuli and internal intention). Additionally, in Stroop task, using Frontoparietal network as seed, Water Aerobics group exhibited a stronger correlation between Left Posterior Parietal Lobe (specialized in word meaning, representing motor actions, motor planning directed to objects, and general perception) and different cerebellar regions (linked to object mirroring). Conclusion Our study provides evidence of differences in functional connectivity between older adults who have received training in a mind–body practice (Tai Chi) or in an aerobic physical activity (Water Aerobics) when performing attentional and working memory tasks, as well as during resting state.